Oil palm seeds tolerance to cryopreservation - Camillo, Julcéia; Luis, Zanderluce Gomes; Scherwinski-Pereira, Jonny Everson (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to evaluate the oil palm (Elaeis guineensis) seed tolerance to cryopreservation. Five genotypes (CM589, C7201, C2528, C2001, and C2501) were evaluated with or without exposure to liquid nitrogen for seven days. Treatments were replicated three times with ten seeds per replicate. Serial anatomical cuts were made to compare the effect of treatments on zygotic embryos. For CM589 and C2528, the exposition to liquid nitrogen accelerated and increased seed germination, respectively. For C2501, liquid nitrogen had no effect. For C7201, liquid nitrogen reduced seed germination (90.7%) compared to the check (100%). Anatomically, the liquid nitrogen did not interfere with embryonic tissue differentiation or development during germination